The association between sleep duration trajectories and intrinsic capacity in middle-aged and older adults in China: a longitudinal Chinese study assessing healthy aging - Yang, Chengzhen; Chen, Xi; Wan, Xia; Cai, Yinghua (Frontiers in Medicine, 2025)
BackgroundPrevious studies have focused mostly on the association between a single measurement of nighttime sleep duration and intrinsic capacity, making revealing the dynamic interaction between nighttime sleep duration and nap duration as individuals age throughout their lifespan difficult. This study aimed to identify the joint developmental trajectories of nighttime sleep duration and nap duration and explore their associations with intrinsic capacity.MethodData from 5,618 participants in the China Health and Retirement Longitudinal Study across three waves (2011, 2013, 2015) were analyzed. Group-based multi-trajectory modeling was employed to identify joint developmental trajectories of nighttime sleep and nap duration, and a binary logistic regression analysis was used to explore the associations between joint developmental trajectories and intrinsic capacity.ResultsFour distinct joint developmental trajectories were identified. Compared with the “Continuous moderate nighttime sleep without napping” trajectory group, the “Persistent short sleep at night without napping” trajectory group (OR = 1.64, 95% CI: 1.26–2.12) exhibited a significantly higher risk of low intrinsic capacity. Conversely, the “Double moderate sleep duration” trajectory group was more likely to have high intrinsic capacity (OR = 0.81, 95% CI: 0.68–0.96). No significant association was observed in the “Persistent short nighttime sleep with moderate napping” trajectory group (OR = 1.00, 95% CI: 0.82–1.21).ConclusionPersistent short nighttime sleep patterns are significantly associated with a risk of low intrinsic capacity, whereas moderate napping may offset the adverse effects of persistent short nighttime sleep on intrinsic capacity. Conversely, a combined pattern of moderate nighttime sleep and moderate napping appears most beneficial for maintaining high intrinsic capacity. This study suggests that scientifically planning sleep duration is important for maintaining high intrinsic capacity, providing new theoretical references for optimizing the “dual-mode sleep” management strategy for middle-aged and older adults.